An overview of selective laser sintering and melting research using bibliometric indicators. Issue 4 (2nd October 2018) - Ameen, Wadea; Ghaleb, Atef M.; Alatefi, Moath; Alkhalefah, Hisham; Alahmari, Abdulrahman
ABSTRACT: The aim of this paper is to present an overview of published research in selective laser sintering/melting (SLS/M), by using bibliometric indicators. Bibliometrics is the quantitative statistical analysis of written publications, such as articles or books. It is useful for displaying and classifying information according to selected variables, such as authors, journals, citations, countries, and institutions. This type of review provides a clear picture of research in a targeted area, such as the most cited research, author with most publications, journal with most published papers, and universities and countries producing the largest amount of research in the target area. The Web of Science database was used to collect data on the topic of interest. The results reveal that the Rapid Prototyping journal is the most productive journal in this field, where the Huazhong University Science Technology is the most effective institution. Also China is the most productive country, whereas USA is the most influential country.